The Role of Digitalization in Expanding MSME Market Access - Uly Mabruroh Halida; Cici' Wilantini (Quantitative Economics and Management Studies, 2022)
The pandemic period has succeeded in shifting many habits, one of which is the direct market which has turned into an online market. Digital transformation is important to implement today in order to keep up with market trends. The convenience and practicality that are the advantages of the digital system are able to expand market access for MSMEs. One of the MSMEs that is trying to implement digitalization to expand market access is Apotek Anugerah Bluto Medika. The purpose of this study is to analyze the role of digitization in expanding market access for Apotek Anugerah Bluto Medika and analyze its marketing prospects through the involvement of digitalization. This research is a descriptive qualitative research. Data obtained from interviews, observations, and documentation. The results of this study show that digitalization has an important role for Apotek Anugerah Bluto Medika, especially in the field of marketing, namely to attract old customers and new customers to find out more about Apotek Anugerah Bluto Medika through the digitalization transformation process that is being developed. The prospects obtained by pharmacies from this digitization process are in the form of convenience in providing information, consulting and social services, community aspirations services in the form of criticism and suggestions, product services and so on to the wider community regarding health. Although it cannot be denied that there are still some obstacles faced in the digital transformation process.